Effect Of Early Quantitative Feed Restriction On Growth And Production Indicators Of Broiler Chickens - Basil M. Ibrahim; Luma K. Bandr; Mohammed A. Hussein; Waleed Khalid Al-Hayani (University of Thi-Qar Journal of agricultural research, 2025)
This study was conducted in the poultry field, College of Agricultural Engineering Sciences / University of Baghdad, during the period from 1/5/2023 to 5/6/2023. The aim of the study is to investigate the effects of feed restrictionsat an early age on the production performance of broiler chickens. Three hundred one-day-old Ross 308 chicks with an average initial weight of 46 g were used for the study and divided into four treatments. Each treatment consisted of seventy-five birds divided into three replicates of twenty-five birds each. The four treatments included the following: The first treatment (T1): Ad libitum feeding during the study period of 1 to 35 days. The second, third and fourth treatments (T2, T3 and T4): Ad libitum feeding during the first week of life (1-7 days), restriction of feed by 15, 25 and 35% respectively during the period of 8-21 days, then ad libitum feeding during the remaining period (22-35 days). The results showed a significant decrease (P<0.01) in body weight at 35 days of age and weight gain over the entire period (1-35 days) at T2, T3 and T4 compared to T1, with T3 having an advantage over T2 and T4. With a significant decrease (P<0.01) in T2, T3 and T4 in feed intake over the entire period (1-35 days) compared to T1, with a significant decrease in T3 and T4 compared to T2. At the same time, no significant differences were observed in feed utilization, dressing percentage and percentage of carcass parts and some internal organs. These results therefore indicate the possibility of reducing nutritional and production costs through early feed restrictions without negatively affecting production performance.